Das Schülerlabor als Ort der Informatiklehrerbildung - Schulte, Carsten (INFOS)

Joint mode estimation in multi-label classification by chaining - Dembczynski, K.; Waegeman, W.; Hüllermeier, Eyke (In Proceedings ECML Workshop on Collective inference and Learning on Structured Data, Athens, Greece)

Prediction of protein localization for specialized compartments using time series kernels - Mernberger, M.; Moog, D.; Stork, S.; Zauner, S.; Maier, U.; Hüllermeier, Eyke (In Proceedings GCB-2011 German Conference on Bioinformatics Munich, Germany)

All your clouds are belong to us: security analysis of cloud management interfaces - Somorovsky, Juraj; Heiderich, Mario; Jensen, Meiko; Schwenk, Jörg; Gruschka, Nils; Lo Iacono, Luigi (Proceedings of the 3rd ACM workshop on Cloud computing security workshop - CCSW '11)

On the effectiveness of XML Schema validation for countering XML Signature Wrapping attacks - Jensen, Meiko; Meyer, Christopher; Somorovsky, Juraj; Schwenk, Jörg (2011 1st International Workshop on Securing Services on the Cloud (IWSSC))

How to break XML encryption - Jager, Tibor; Somorovsky, Juraj (Proceedings of the 18th ACM conference on Computer and communications security - CCS '11)

Sec2: Ein mobiles Nutzer-kontrolliertes Sicherheitskonzept für Cloud-Storage - Meyer, Christopher; Somorovsky, Juraj; Driessen, Benedikt; Schwenk, Jörg; Tran, Thang; Wietfeld, Christian

Volume Studio: Flexible Multi-Volume Ray Casting Pipeline mit nahtlos integriertem Rapid Prototyping von Shadern. - Arens, Stephan; Domik, Gitta (INFORMATIK 2011 – 41. Jahrestagung der Gesellschaft für Informatik.)

Mixing Bottom-Up and Top-Down XPath Query Evaluation - Benter, Markus; Böttcher, Stefan; Hartel, Rita (East European Conference on Advances in Databases and Information Systems)

Updates on Grammar-Compressed XML Data - Bätz, Alexander; Böttcher, Stefan; Hartel, Rita (Advances in Databases - 28th British National Conference on Databases, BNCOD 28, Revised Selected Papers)

TraCX: Transformation of Compressed XML - Böttcher, Stefan; Hartel, Rita; Stey, Sebastian (Advances in Databases - 28th British National Conference on Databases, BNCOD 28, Revised Selected Papers)

Search and Modification in Compressed Texts - Böttcher, Stefan; Bültmann, Alexander; Hartel, Rita (2011 Data Compression Conference)

Enhancing XML-cache Efficiency by XML Compression - Böttcher, Stefan; Fernhomberg, Lars; Hartel, Rita (WEBIST 2011, Proceedings of the 7th International Conference on Web Information Systems and Technologies)

Reducing Data Transfer by Combining XML-Compression and XML-Caching - Böttcher, Stefan; Fernhomberg, Lars; Hartel, Rita (Web Information Systems and Technologies - 7th International Conference, WEBIST 2011, Revised Selected Papers)

Comparing methods for knowledge-driven and data-driven fuzzy modeling: A case study in textile industry - Nasiri, M.; Hüllermeier, Eyke; Senge, Robin; Lughofer, E. (in Proceedings IFSA-2011 World Congress of the International Fuzzy Systems Association, Surabaya and Bali Island, Indonesia)

On-line redundancy deletion in evolving fuzzy regression models using a fuzzy inclusion measure - Lughofer, E.; Hüllermeier, Eyke (in Proceedings EUSFLAT-2011 7th International Conference on the European Society for Fuzzy Logic and Technology, Aix-les-Bains, France)

Choquistic regression: Generalizing logistic regression using the Choquet integral - Fallah Tehrani, A.; Cheng, W.; Hüllermeier, Eyke (in Proceedings EUSFLAT-2011 7th International Conference on the European Society for Fuzzy Logic and Technology, Aix-les-Bains, France)

Transdisciplinary collaboration and lifelong learning: fostering and supporting new learning opportunities - Domik, Gitta; Fischer, Gerhard (Rainbow of computer science)

Namenlemmatisierung in der Web-Datenbank mittelalterlicher und frühneuzeitlicher Universitätsmatrikel - Böttcher, Stefan; Hartel, Rita; Hawicks, Heike (XXIV ICOS Internationales Kongress für Namensforschung)

How useful is computer graphics for medical diagnoses? - Domik, Gitta; Arens, Stephan; Scharlau, Ingrid; Hilkenmeier, Frederic (INFORMATIK 2011 – Informatik schafft Communities)

Multimaterialsysteme höchstfest verbunden - Lauter, Christian; Sarrazin, M.; Tröster, Thomas (Adhäsion – Kleben und Dichten)

Mechatronisches System zur Bestimmung der Restlebensdauer von Faserverbund-Leichtbaustrukturen am Beispiel einer Lauffeder - Frantz, Meike; Stübbe, O.; Lauter, Christian; Schrange, J.; Tröster, Thomas

Herstellung von belastungsgerechten Strukturbauteilen mittels partieller induktiver Härtung - Thomas, D.; Block, H.; Tröster, Thomas; Krogmeier, J.

Automobilleichtbau durch höchstfeste Multimaterialsysteme - Marten, Thorsten; Lauter, Christian; Tröster, Thomas (Ingenieurspiegel)

Belastungsangepasste Strukturbauteile für Automobile aus höchstfesten Werkstoffen und Hybridwerkstoffen - Lauter, Christian; Thomas, D.; Frantz, Meike; Niewel, J.; Tröster, Thomas (Werkstoffe in der Fertigung – Die Fachzeitschrift für technische Führungskräfte)

Hybrid structures for tailored structural automotive components - Lauter, Christian; Frantz, Meike; Siewers, Bernd; Tröster, Thomas (JEC Composites Magazine)

Production of load-adapted lightweight designs by partial hardening - Thomas, D.; Block, H.; Tröster, Thomas

In situ characterization of the deformation and failure behavior of non-stochastic porous structures processed by selective laser melting - Gorny, B.; Niendorf, T.; Lackmann, J.; Thoene, M.; Tröster, Thomas; Maier, H.J. (Materials Science and Engineering: A)

Großserientaugliche Herstellung höchstfester Hybridwerkstoffe durch Prepregpressen - Lauter, Christian; Frantz, Meike; Tröster, Thomas (Lightweight Design)

Advanced manufacturing technologies for automotive structures in multi-material design consisting of high-strength steels and CFRP - Frantz, Meike; Lauter, Christian; Tröster, Thomas

Höchstfeste Hybridwerkstoffe aus Stahl und Faserverbundkunststoffen - Lauter, Christian; Frantz, Meike; Marten, Thorsten; Tröster, Thomas; Bach, G.; Seliger, G. (Konstruktion: Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Schadensdetektion in hybriden Metall-Faserverbundkunststoff-Konstruktionen - Frantz, Meike; Lauter, Christian; Tröster, Thomas (Konstruktion: Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Fluidized bed heating of blanks for the hot forming process - Marten, Thorsten; Tröster, Thomas; Adelbert, S.; Kadim, A.

Hybridstrukturen für den automobilen Leichtbau - Tröster, Thomas; Lauter, Christian

Großserientaugliche Herstellung von Hybridwerkstoffen durch Prepregpressen - Lauter, Christian; Frantz, Meike; Tröster, Thomas (Lightweight Design)

Continuous phase stabilization and active interferometer control using two modes - Jotzu, Gregor; Bartley, Tim; Coldenstrodt-Ronge, Hendrik B.; Smith, Brian J.; Walmsley, Ian A. (Journal of Modern Optics)

Multivariate modeling to identify patterns in clinical data: The example of chest pain - Hirsch, O.; Bösner, S.; Hüllermeier, Eyke; Senge, R.; Dembczynski, K.; Donner-Banzhoff, N. (BMC Medical Research Methodology)

Preferences in AL: An overview - Domshlak, C.; Hüllermeier, Eyke; Kaci, S.; Prade, H. (Artificial Intelligence)

Fuzzy machine learning and data mining - Hüllermeier, Eyke (WIREs Data Mining and Knowledge Discovery)

SEGA: Semi-global graph alignment for structure-based protein comparison - Mernberger, M.; Klebe, G.; Hüllermeier, Eyke (IEEE/ACM Transactions of Computational Biology and Bioinformatics)

Superposition and alignment of labeled point clouds - Fober, T.; Glinca, S.; Klebe, G.; Hüllermeier, Eyke (IEEE/ACM Transactions on Computational Biology and Bioinformatics)

Load Balancing in P2P Networks: Using Statistics to Fight Data and Execution Skew - Warneke, Daniel; Dannewitz, Christian (Journal of Advances in Information Technology)

Fuzzy sets in machine learning and data mining - Hüllermeier, Eyke (Applied Soft Computing Journal)

Top-down induction of fuzzy pattern trees - Senge, Robin; Hüllermeier, Eyke (IEEE Transactions on Fuzzy Systems)

Simulation of Deep Drawing of Carbon Fibre Prepregs - Hankeln, Frederik; Mahnken, Rolf (PAMM)

Werberecht (Gesetze, Urteile, Fälle und Lösungen, Sprachfassung auf interaktiver CD) - Krimphove, Dieter

A New Approach for Analyzing Convergence Algorithms for Mobile Robots - Cord-Landwehr, Andreas; Degener, Bastian; Fischer, Matthias; Hüllmann, Martina; Kempkes, Barbara; Klaas, Alexander; Kling, Peter; Kurras, Sven; Märtens, Marcus; Meyer auf der Heide, Friedhelm; Raupach, Christoph; Swierkot, Kamil; et al. (Automata, Languages and Programming)
Given a set of n mobile robots in the d-dimensional Euclidean space, the goal is to let them converge to a single not predefined point. The challenge is that the robots are limited in their capabilities. Robots can, upon activation, compute the positions of all other robots using an individual affine coordinate system. The robots are indistinguishable, oblivious and may have different affine coordinate systems. A very general discrete time model assumes that robots are activated in arbitrary order. Further, the computation of a new target point may happen much earlier than the movement, so that the movement is based on outdated information about other robot's positions. Time is measured as the number of rounds, where a round ends as soon as each robot has moved at least once. In [Cohen, Peleg: Convergence properties of gravitational algorithms in asynchronous robot systems], the Center of Gravity is considered as target function, convergence was proven, and the number of rounds needed for halving the diameter of the convex hull of the robot's positions was shown to be O(n^2) and Omega(n). We present an easy-to-check property of target functions that guarantee convergence and yields upper time bounds. This property intuitively says that when a robot computes a new target point, this point is significantly within the current axes aligned minimal box containing all robots. This property holds, e.g., for the above-mentioned target function, and improves the above O(n^2) to an asymptotically optimal O(n) upper bound. Our technique also yields a constant time bound for a target function that requires all robots having identical coordinate axes.

Die Auswirkung verschiedener Klebungen auf das Verhalten eines piezoelektrischen Wandlers - Bause, Fabian
Die Modellierung bzw. das virtuelle Design von Ultraschallwandlern spielt gerade im Hinblick auf die Mannigfaltigkeit ihrer Einsatzgebiete und die stetig wachsenden Anforderungen der Industrie eine Schlüsselrolle bei der Entwicklung piezoelektrischer Sensor- und Aktorsysteme. Der jeweils für eine spezielle Anwendung zu erreichende Grad der Realitätsnähe der eingesetzten Modelle ist dabei essentielle Voraussetzung für die Legitimation des virtuellen Designs. Neben idealisierten Strukturen, welche der Modellbildung unweigerlich anhaften, wird die Realitätsnähe wesentlich durch die genutzten Materialmodelle und deren Parametrisierung beeinflusst. Viele Arbeiten wurden aus diesem Grund auf dem Gebiet der akustischen Materialdaten-bestimmung sowohl passiver als auch aktiver Materialien durchgeführt. Ein Ultraschallwandler besteht nun aus einer Komposition von aktiven und passiven Elementen, welche z. B. mittels Klebungen zusammengefügt werden. Aktuelle Praxis ist die Vernachlässigung der Klebschichteigenschaften oder ggf. eine Korrektur der durch die Klebschichtdicke hervorgerufene Frequenzverschiebung durch eine virtuelle Vergrößerung eines der Fügeteile. Dabei werden die Koppelbedingungen zwischen den gefügten Materialien als ideal angenommen, was in der Realität jedoch nicht der Fall ist. Klebungen sind weder isotrop noch homogen aufgebaut. Des Weiteren ist ihre Dicke sehr klein, was in der Computersimulation dazu führt, dass sie über effektive Parameter und stark vereinfachte Modelle beschrieben werden.

Von der Messaufgabe zum Sensorsystem - Henning, Bernd
Ultraschallsensoren werden heute in der Industrie vielfach erfolgreich für die verschiedensten Messaufgaben eingesetzt und ständig weiterentwickelt. Wesentliche aktuelle Entwicklungen zielen auf die Erweiterung der Funktionalität (adaptierbare Abstrahlcharakteristik, scannende Sensoren …), die Erhöhung der Zuverlässigkeit, die Miniaturisierung sowie auf die Reduktion der Gerätekosten (Materialsubstitution) und Fertigungskosten (Konstruktion und Montage).

Ultrasonic Nondestructive Testing of composite materials using disturbed coincidence conditions - Bause, Fabian; Olfert, Sergei; Schröder, Andreas; Rautenberg, Jens; Henning, Bernd; Moritzer, Elmar (Journal of Electronic Measurement and Instrument)

Analyzing the effect of adhered metal electrodes on piezoelectric elements using different types of adhesives - Bause, Fabian; Rautenberg, Jens; Henning, Bernd
Modeling and simulation play a key-role in computer-assisted design of ultrasonic sensors. The accuracy of those numerical or analytical models highly depends on the material dataset chosen as well as on the digitized simplified geometry. Thus, researchers worked on techniques how to measure material datasets of piezoceramics or passive materials (i.e. polymers) for use in simulation [Rau08] [Rup09]. Most computer models neglect the influence of adhesive bonds between those active and passive material components used to form a complete ultrasonic transducer and thus imply perfect interface layers. To gain a more accurate model one need to go further and consider non-perfect interface layers between assembly parts. Because adhesive bonds are neither necessarily isotropic nor homogeneous and their geometric dimensions are very small, we need to define effective material datasets dependent on the model used in simulation. In this contribution the indicator under study is the electric impedance of the active element. We will show the influence of different adhesives used to adhere metal electrodes on piezoceramic discs. Therefore, we use several different types of adhesives (epoxies, cyanoacrylates and perfluorpolyether grease) and different sizes of piezoceramic discs (PIC 255, manufacturer: PI Ceramic GmbH) of the same batch (thickness, diameter). The electrodes have been cut from one plate made of stainless steel using a laser to avoid uncertainty effects due to variations in material-parameters. The probes have been prepared in an air-conditioned Lab with constant temperature and humidity. The indicators considered to identify the effect of those different adhesive films are extracted from the electric impedance of the electromechanical converter.

Ultrasonic distance sensors - An overview and trends - Henning, Bernd; Schröder, Andreas (Journal of Electronic Measurement and Instrument)
Nowadays ultrasonic distance sensors are widely used in automobiles, robotics and in industrial automation. Some functional principles of usable transducers for airborne ultrasonic distance measurements are shown. As every sensor principle, ultrasonic distance sensors have pros and cons which lead to some problems and challenges described below. For the main challenges (crosstalk and blind zone) some trends and solutions are presented.

Vergleich zwischen der Schlierenmethode nach Toepler und der Hintergrundschlierenmethode zur Bestimmung akustischer Grössen eines Ultraschallwandlers - Olfert, Sergei; Henning, Bernd
Es gibt unterschiedliche Methoden, um räumliche Schallwechseldruckverteilungen in Flüssigkeiten zu erfassen. Viele dieser Verfahren haben zwei Nachteile. Sie sind zum einen invasiv, beeinflussen somit die sich ausbreitende Ultraschallwelle, und zum anderen sehr zeitaufwendig. Die Visualisierung von Ultraschallfeldern mittels Schlierenmethode ist eine schnelle und einfache Methode, um zweidimensionale Schallfelder nichtinvasiv zu analysieren. Ein besonderer Vorteil besteht darin, dass man unmittelbar resultierende Veränderungen im Schallfeld zum Beispiel bei Frequenzänderung, Sensorausrichtung… beobachten kann. In diesem Beitrag werden zwei dieser Verfahren vorgestellt. Die modifizierte Schlierenmethode nach Toepler, das im Weiteren als modifizierte Schlierenmethode bezeichnet wird, und die Hintergrund-schlierenmethode, das sich bisher hauptsächlich zur Strömungsvisualisierung etabliert hat [1]. Im ersten Teil werden beide Messverfahren erläutert, die realisierten Messaufbauten sowie Einsatzmöglichkeiten für die Schallfeldcharakterisierung kurz vorgestellt. Im zweiten Teil werden beide Verfahren verglichen und die Vor- und Nachteile bezüglich ausgewählter Messaufgaben bewertet.

Utilizing an Analytical Approximation for c44E to Enhance the Inverse Method for Material Parameter Identification of Piezoceramics - Rautenberg, Jens; Rupitsch, Stefan J.; Henning, Bernd; Lerch, Reinhard (7th International Workshop on Direct and Inverse Problems in Piezoelectricity)
There has been a lot of progress in finding measurable quantities of high in- formation content for the inverse determination of piezoelectric material properties. Since some material parameters (mainly \textgreek{e}S 11, e15and cE 44) do not or only marginally influence the electrical impedance over frequency, it is not sufficient to look only at the electri- cal impedance of discoidal piezoceramics [1]. Moreover, the parameter sensitivities vary with respect to the diameter--thickness ratio of the disc and the design of an ultrasonic transducer's piezoceramic has to match other requirements than those of a good material characterization [2, 3]. That is why it is still desirable to find model based approaches for parameter identification that either keep the technical effort low (e.g., only an impedance measurement) or increase speed of the inversion procedure. In this contribution we answer the question if an additional analytical approximation of cE 44, strictly following the ideas of Theocaris [4], in conjunction with a single measured elec- trical impedance will be sufficient for an accurate simulation of both, electrical impedance and surface normal velocity of a piezoceramic disc. Thereby, the remaining parameters are identified by means of the Inverse Method. Furthermore, we use the parameter ap- proximation as an initial guess and limiting boundary to speed up the inverse algorithm if both, electrical impedance and surface normal velocity are taken into account within the optimization procedure.

Luftultraschall-Abstandsmessung mit verkürztem Mindestabstand - Schröder, Andreas; Henning, Bernd
Bei der Luftultraschall-Abstandsmessung mit einem einzelnen Schallwandler ist der Mindestabstand durch die Sendesignaldauer und die Ausschwingzeit des Schallwandlers begrenzt. Daher führt die Verwendung von codierten Sendesignalen, wie sie z.B. für die Unterscheidung mehrerer Sender genutzt werden können, im Allgemeinen zu einer Vergrößerung des Mindestabstandes. Dieser Beitrag zeigt, dass der Mindestabstand bei codierten Sendesignalen durch eine geeignete Signalverarbeitung, bei der eine Trennung des Sende- und Empfangssignals erfolgt, deutlich verringert werden kann.

Model based separation of transmitted and received signal for single transducer distance measurement applications - Schröder, Andreas; Henning, Bernd
Simultaneous transmitting and receiving (STaR) enhances the utilization of single transducer ultrasound measurement systems. In distance measurement applications the dead zone can be reduced to nearly zero, independent of the transmitted signal. So it is possible to transmit codedsignals to identify different sensors without increasing the minimum distance. The electrical transducer signal consists of the electrical transmitted and received signal. A separation of these two signals can be done with a mathematical model of the electrical system. For this purpose it is necessary to digitize the electrical transducer signal. Due to the relative small amplitude of the received signal compared to the transmitted signal amplitude, a high resolution analog to digital converter (ADC) is needed. This leads to high requirements for the ADC. The necessary resolution limits the sample rate of the ADC. By down mixing the transducer signal using a coherent quadrature demodulation (CQD), as used in many high frequency ultrasound applications, the sample rate of the ADC can be reduced. In this contribution an airborne ultrasound distance measurement system with reduced dead zone is used to analyze the effects of this concept to the signal conditioning, system identification and system performance. The approach is compared with a system without CQD and an ADC with a lower resolution but a higher sample rate. By analyzing the pros and cons of both systems the usability of a CQD based system for a STaR application is evaluated. The distance measurement system used for the experiments is based on a 40 kHz airborne ultrasonic transducer. A gyrator based transmit amplifier delivers a system bandwidth of about 10 kHz. In the experiments, coded transmitted signals are used to measure the distance to a metal reflector. The main objectives are short distances between 0 mm and 200 mm. Here a separation of transmitted and received signal is necessary. The reflector distance is calculated by a cross correlation between transmitted and received signal.

Finite element simulation of single ultrasonic transducer with segmented electrodes to adjust the directional characteristic - Unverzagt, Carsten; Henning, Bernd
For many applications like level measurement and industry robotics it is of advantage if the directional characteristic of an ultrasonic transducer is changeable or adaptable for the improvement of spatial resolution. Often this goal is reached with the use of ultrasonic transducer arrays, which elements are driven with phase shifted excitation signals. One disadvantage of these solutions is the great effort for building such an array and the multi-channel sensor electronics. In this contribution the directional characteristic of a single air transducer with segmented electrodes is analyzed. Therefore a variable script based finite element model is used to discover the influence of different electrode configurations on the directional characteristic of a single piezoceramic transducer. Especially the influence on the angle of beam and the near field length are evaluated. The used variable model permits an optimization of the configuration with regards to the mentioned criteria. The findings will be used for the development of a level measurement system for bulk solids.
Keywords: Elektrode

Robuster Selbsttest mit Diagnose - Cook, Alejandro; Hellebrand, Sybille; Indlekofer, Thomas; Wunderlich, Hans-Joachim (5. GMM/GI/ITG Fachtagung "Zuverlässigkeit und Entwurf")

An exact algorithm for F-measure maximization - Dembczynski, K.; Waegeman, W.; Cheng, W.; Hüllermeier, Eyke (In Proceedings NIPS-2011, 25th Annual Conference on Neural Information Processing Systems, Granada, Spain)

Preference-based policy iteration: Leveraging preference learning for reinforcement learning - Cheng, W.; Fuernkranz, J.; Hüllermeier, Eyke; Park, S.H. (Proceedings ECML/PKDD-2011, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, Athens, Greece,)

Learning from label preferences - Fürnkranz, J.; Hüllermeier, Eyke (in Proceedings DS-2011, 14th International Conference on Discovery Science, number 6926 in LNAI)

Learning monotone nonlinear models using the Choquet integral - Fallah Tehrani, A.; Cheng, W.; Dembczynski, K.; Hüllermeier, Eyke (In Proceedings ECML/PKDD-2011, European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases, Athens, Greece,)

Preference-based CBR: First steps toward a methodological framework - Hüllermeier, Eyke; Schlegel, P. (In Proceedings ICCBR-2011, 19th International Conference on Case-Based Reasoning, number 6880 in LNAI)

Anwendungsszenarien als Werkzeug zur (V) Ermittlung des Nutzens von corporate social software - Trier, Matthias; Richter, Alexander; Mörl, Susanne; Koch, Michael (10th International Conference on Wirtschaftsinformatik)

CYBEREMOTIONS – Collective Emotions in Cyberspace - Ahn, Junghyun; Borowiec, Anna; Buckley, Kevan; Cai, Di; Chmiel, Anna; Czaplicka, Agnieszka; Dąbrowski, Grzegorz; Garas, Antonios; Garcia, David; Gobron, Stéphane; Hillmann, Robert; Hołyst, Janusz; et al. (Procedia Computer Science)

Dynamische Analyse von Netzwerken elektronischer Kommunikation. Kann der Zentralität getraut werden? - Trier, Matthias; Bobrik, Annette (Netzwerkanalyse und Netzwerktheorie)

Anwendungsszenarien als Werkzeug zur (V)Ermittlung des Nutzens von Corporate Social Software - Richter, Alexander; Mörl, Susanne; Trier, Matthias; Koch, Michael

Imaging of the Ferroelectric Domain Structures by Confocal Raman Spectroscopy - Berth, Gerhard; Hahn, Wjatscheslaw; Wiedemeier, Volker; Zrenner, Artur; Sanna, Simone; Schmidt, Wolf Gero (Ferroelectrics)

Influence of Na adsorption on the quantum conductance and metal-insulator transition of the In-Si(111)(4×1)–(8×2) nanowire array - Schmidt, Wolf Gero; Babilon, M.; Thierfelder, C.; Sanna, S.; Wippermann, S. (Physical Review B)

Group-VII point defects in ZnSe - dos Santos, L. S.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Preserving Charge and Oxidation State of Au(III) Ions in an Agent-Functionalized Nanocrystal Model System - Müllegger, Stefan; Schöfberger, Wolfgang; Rashidi, Mohammad; Lengauer, Thomas; Klappenberger, Florian; Diller, Katharina; Kara, Kamuran; Barth, Johannes V.; Rauls, Eva; Schmidt, Wolf Gero; Koch, Reinhold (ACS Nano)

Electrically Detected Electron-Spin-Echo Envelope Modulation: A Highly Sensitive Technique for Resolving Complex Interface Structures - Hoehne, Felix; Lu, Jinming; Stegner, Andre R.; Stutzmann, Martin; Brandt, Martin S.; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Letters)

Microscopic structure and energy transfer of vacancy-related defect pairs with Erbium in wide-gap semiconductors - Konopka, A.; Greulich-Weber, S.; Dierolf, V.; Jiang, H.X.; Gerstmann, Uwe; Rauls, E.; Sanna, S.; Schmidt, Wolf Gero (Optical Materials)

Band offsets in cubic GaN/AlN superlattices - Mietze, C.; Landmann, M.; Rauls, E.; Machhadani, H.; Sakr, S.; Tchernycheva, M.; Julien, F. H.; Schmidt, Wolf Gero; Lischka, K.; As, Donat Josef (Physical Review B)

Driving forces for the adsorption of cyclopentene on InP(001) - Favero, P.P.; Ferraz, A.C.; Schmidt, Wolf Gero; Miotto, R. (Surface Science)

Asymmetric saddling of single porphyrin molecules on Au(111) - Müllegger, S.; Rashidi, M.; Lengauer, T.; Rauls, E.; Schmidt, Wolf Gero; Knör, G.; Schöfberger, W.; Koch, R. (Physical Review B)

Methane adsorption on graphene from first principles including dispersion interaction - Thierfelder, C.; Witte, M.; Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (Surface Science)

Bipartite ranking through minimization of univariate loss - Kotlowski, W.; Dembczynski, K.; Hüllermeier, Eyke (in Proceedings ICML-2011, 28th International Conference on Machine Learning, Washington, USA)

Memory Virtualization for Multithreaded Reconfigurable Hardware - Agne, Andreas; Platzner, Marco; Lübbers, Enno (Proceedings of the International Conference on Field Programmable Logic and Applications (FPL))

Design and architectures for dependable embedded systems - Henkel, Jörg; Hedrich, Lars; Herkersdorf, Andreas; Kapitza, Rüdiger; Lohmann, Daniel; Marwedel, Peter; Platzner, Marco; Rosenstiel, Wolfgang; Schlichtmann, Ulf; Spinczyk, Olaf; Tahoori, Mehdi; Bauer, Lars; et al. (Proceedings of the seventh IEEE/ACM/IFIP International Conference on Hardware/software Codesign and system synthesis - CODES+ISSS '11)

Complex Queries in P2P Networks with Resource-Constrained Devices - Dannewitz, Christian; Biermann, Thorsten; Dräxler, Martin; Karl, Holger (Journal of Advances in Information Technology)

Vibrational properties of the LiNbO3 z-surfaces - Sanna, S.; Berth, G.; Hahn, W.; Widhalm, A.; Zrenner, A.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)

Combined ab initio and classical potential simulation study on silicon carbide precipitation in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, J. K. N.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Barium titanate ground- and excited-state properties from first-principles calculations - Sanna, S.; Thierfelder, C.; Wippermann, S.; Sinha, T. P.; Schmidt, Wolf Gero (Physical Review B)

Modellbasierte Konzipierung eines hybriden Energiespeichersystems für ein autonomes Schienenfahrzeug - Gausemeier, Jürgen; Dumitrescu, Roman; Tschirner, Christian; Stille, Karl Stephan Christian (Tag des Systems Engineering)
Die Kommunikations- und Informationstechnik eröffnet neue Möglichkeiten zur Erweiterung und Optimierung der Systemfunktionalität mechatronischer Systeme. Die erfolgreiche Entwicklung dieser fortgeschrittenen mechatronischen Systeme bedarf sowohl einer besonderen Strukturierung der Informationsverarbeitung als auch einer geeigneten modellbasierten Entwurfstechnik. SysML und CONSENS eignen sich für den Entwurf derartiger Systeme. Die Anwendung von CONSENS wird anhand eines Demonstrators vertieft.
Keywords: Produktentstehung; HES; Hybrider Energiespeicher; CONSENS; SysML; SFB614; LEA-Publikation; Eigene

Aus dem Deutschen ins Italienische: U. Dirk und A. Wagner, Filosofia dell’interpretazione. Principi, sviluppi, caratteristiche

Aus dem Deutschen ins Italienische: G. Abel, Il rapporto interno tra linguaggio, comunicazione, mondo della vita e scienza

Adorno, T. W., Einführung in die Dialektik, Frankfurt a.M. 2010 - Ficara, Elena (Hegel-Studien)

Skeptizismus und Philosophie. Kant, Fichte, Hegel - Ficara, Elena (Rivista di storia della filosofia)

Metaphysik in der zeitgenössischen Hegelrezeption - Ficara, Elena (Hegel Jahrbuch)

Die Begründung der Philosophie im Deutschen Idealismus

Optimierte Regelung für mobile Elektromotoren - Wallscheid, Oliver; Peters, Wilhelm; Böcker, Joachim (Aktuelle Technik)

Current controller with defined dynamic behavior for an interior permanent magnet synchronous motor - Peters, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (IECON 2011-37th Annual Conference of the IEEE Industrial Electronics Society)

What determines influenza vaccination take-up of elderly Europeans? - Schmitz, Hendrik; Wübker, Ansgar (Health Economics)

Direct evidence of risk aversion as a source of advantageous selection in health insurance - Schmitz, Hendrik (Economics Letters)

Why are the unemployed in worse health? The causal effect of unemployment on health - Schmitz, Hendrik (Labour Economics)

Profit efficiency and ownership of German hospitals - Herr, Annika; Schmitz, Hendrik; Augurzky, Boris (Health Economics)

Digital Control Strategy for Multi-Phase Interleaved Boundary Mode and DCM Boost PFC Converters - Grote, Tobias; Figge, Heiko; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. IEEE Energy Conversion Congress and Exposition (ECCE))

Overcurrent Protection for the LLC Resonant Converter with Improved Hold-Up Time - Figge, Heiko; Grote, Tobias; Fröhleke, Norbert; Böcker, Joachim; Schafmeister, Frank (Proc. 26th IEEE Applied Power Electronics Conference (APEC))

Unidirektionaler AC-AC-Matrixkonverter mit Dreipunkt Ein- und Ausgangsstufe - Schafmeister, Frank; Kolar, Johann